Identification of Quantitative Disease Resistance Loci Toward Four Pythium Species in Soybean - Clevinger, Elizabeth M.; Biyashev, Ruslan; Lerch-Olson, Elizabeth; Yu, Haipeng; Quigley, Charles; Song, Qijian; Dorrance, Anne E.; Robertson, Alison E.; Saghai Maroof, M. A. (Frontiers in Plant Science, 2021)
In this study, four recombinant inbred line (RIL) populations were screened for their response to infection by Pythium sylvaticum, Pythium irregulare, Pythium oopapillum and Pythium torulosum. The parents, PI 424237A, PI 424237B, PI 408097 and PI 408029, had higher levels of resistance to these species in a preliminary screening and were crossed with ‘Williams’, a susceptible cultivar. A modified seed rot assay was used to evaluate RIL populations for their response to specific Pythium species selected for a particular population based on preliminary screenings. Over 2500 single nucleotide polymorphism (SNP) markers were used to construct chromosomal maps to identify regions associated with resistance to Pythium species. Several minor and large effect quantitative disease resistance loci (QDRL) were identified including one large effect QDRL on chromosome 8 in the population of PI 408097 x Williams, which was identified by two different disease reaction traits in P. sylvaticum, P. irregulare and P. torulosum. Another large effect QDRL was identified on chromosome 6 in the population of PI 408029 x Williams, and conferred resistance to P. sylvaticum and P. irregulare. These large effect QDRL will contribute towards the development of improved cultivars with higher levels of resistance to these common soil-borne pathogens.